2008
DOI: 10.1007/s10544-008-9174-7
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic high viability neural cell separation using viscoelastically tuned hydrodynamic spreading

Abstract: A high viability microfluidic cell separation technique of high throughput was demonstrated based on size difference continuous mode hydrodynamic spreading with viscoelastic tuning. Using water with fluorescent dye as sample fluid and in parallel introducing as elution a viscoelastic biocompatible polymer solution of alginic sodium, the spreading behavior was investigated at different polymer concentrations and flow rates. Particle separation was studied in the same detail for 9.9 microm and 1.9 microm latex b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
(45 reference statements)
0
24
0
Order By: Relevance
“…The throughput of our inertial microchip is 1.188 Â 10 7 cells/h, which is a significant improvement compared to using viscoelasticity tuned hydrodynamic spreading. 17 Although the throughput of the inertial chip is slower than the FACS, the throughput capability of our proposed device can be dramatically amplified by parallelizing several microchannels in the same microchip. 19 Compared to FACS, our inertial device is label-free, which may significantly reduce the total processing time and costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The throughput of our inertial microchip is 1.188 Â 10 7 cells/h, which is a significant improvement compared to using viscoelasticity tuned hydrodynamic spreading. 17 Although the throughput of the inertial chip is slower than the FACS, the throughput capability of our proposed device can be dramatically amplified by parallelizing several microchannels in the same microchip. 19 Compared to FACS, our inertial device is label-free, which may significantly reduce the total processing time and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these devices normally run in a batch manner and with a very limited throughput. Apart from DEP, Wu et al 17 also reported on the application of viscoelasticity tuned hydrodynamic spreading on neural cell separation where the microfluidic device works in a continuous and label free manner. Their device could achieve high viability neural cell separation independent of medium dielectric properties.…”
Section: B)mentioning
confidence: 99%
“…To simplify the tuning of cell separation a control channel, placed between the inlets and collectors and controlled with an extra pump, was designed to adapt and adjust to variations due to fabrication. By adding or subtracting fluid from the major flow, the spreading inside the major channel was shifted and finally the particle delivery could be tuned to its desired collectors 24 . …”
Section: Device Designmentioning
confidence: 99%
“…The device was then kept in a closed container with a high humidity environment in a refrigerator at 4ºC overnight. Before cell separation, the device was flushed with sterile PBS buffer 24 . For the experiments, three gastight syringes (Hamilton, Bonaduz, Switzerland) were filled with the fluids (sample and sheaths) and placed on an infusion syringe pump (PHD2000, Harvard apparatus, Boston, MA, USA).…”
Section: Device Fabrication and Fluidic Controlmentioning
confidence: 99%
“…They have rheological properties valuable for thickening and stabilizing, which make them popular in research and in the food, paper, textiles, cosmetics and pharmaceutical industries (Vauchel et al 2008). Their rheological properties have been utilized in microfluidic devices involving ex-vivo mammalian cell preparations (Wu et al 2008). Also, alginate solutions have been introduced directly into the blood circulation of animals in some studies.…”
Section: Introductionmentioning
confidence: 99%